The Role of Mediators in the Development of Longitudinal Mathematics Achievement Associations. Issue 6 (2nd September 2015) - Watts, Tyler W.; Duncan, Greg J.; Chen, Meichu; Claessens, Amy; Davis‐Kean, Pamela E.; Duckworth, Kathryn; Engel, Mimi; Siegler, Robert; Susperreguy, Maria I.
Abstract : Despite research demonstrating a strong association between early and later mathematics achievement, few studies have investigated mediators of this association. Using longitudinal data ( n = 1, 362), this study tested the extent to which mathematics self‐concepts, school placement, executive functioning, and proficiency in fractions and division account for the association between mathematics achievement in first grade and at age 15. As hypothesized, a strong longitudinal association between first‐grade and adolescent mathematics achievement was present (β = .36) even after controlling for a host of background characteristics, including cognitive skills and reading ability. The mediators accounted for 39% of this association, with mathematics self‐concept, gifted and talented placement, and knowledge of fractions and division serving as significant mediators.